Treatment of Mycosis Fungoides with Total Skin Electron Beam Therapy Using Modified Stanford Technique - Ayesha Javed; Javed Mallick; S Asif Ali; Aziz A Siddiqui; Asghar Hussain; Arshad Mehmood; Shabbir Hussain; Abdul Hafeez (Pakistan Journal of Medicine and Dentistry, 2024)
A retrospective review of three patients with mycosis fungoides treated with total skin electron beam therapy , from the year 2007 to 2009 , at the Oncology department, Ziauddin University Hospital.